Universal guidelines for the conversion of proteins and dyes into functional nanothermometers. Issue 9 (30th May 2019) - Spicer, Graham; Efeyan, Alejo; Adam, Alejandro P.; Thompson, Sebastian A.
Abstract: In the last decade, technological advances in chemistry and photonics have enabled real‐time measurement of temperature at the nanoscale. Nanothermometers, probes specifically designed to relay these nanoscale temperature changes, provide a high degree of temperature, temporal, and spatial resolution and precision. Several different approaches have been proposed, including microthermocouples, luminescence and fluorescence polarization anisotropy‐based nanothermometers. Anisotropy‐based nanothermometers excel in terms of biocompatibility because they can be built from endogenous proteins conjugated to dyes, minimizing any system perturbation. Moreover, the resulting fluorescent proteins can retain their native structure and activity while performing the temperature measurement, allowing precise temperature recordings from the native environment or during an enzymatic reaction in any given experimental system. To facilitate the future use of these nanothermometers in research, here we present a theoretical model that predicts the optimal sensitivity for anisotropy‐based thermometers starting with any protein or dye, based on protein size and dye fluorescence lifetime. Using this model, most proteins and dyes can be converted to nanothermometers. The utilization of these nanothermometers by a broad spectrum of disciplines within the scientific community will bring new knowledge and understanding that today remains unavailable with current techniques. Abstract : 2D temperature sensitivity of anisotropy‐based nanothermometers as a function of fluorescence lifetime and Stokes radius. Anisotropy‐based nanothermometers excel in terms of biocompatibility because they can be built from endogenous proteins conjugated to dyes, minimizing any system perturbation. To facilitate the future use of these nanothermometers in several research fields, here we present a theoretical model that predicts the optimal sensitivity for anisotropy‐based thermometers starting with any protein or dye, based on protein size and dye fluorescence lifetime. Using this model, most commonly used proteins and dyes can be converted into nanothermometers.